Linguocultural and Pragmatic Analysis of Forms of Address - Nozigul, Sayidqulova (International Journal on Integrated Education, 2026)
This article analyzes the theoretical and practical aspects of address units and related phenomena. The study examines the linguistic, pragmatic, and sociocultural features of address units and determines their significance in speech communication. Based on the analysis of literature, a comparative study of address units in different languages has been carried out. The results demonstrate the role of address units as a means of reflecting cultural values and social relations. In the conclusion, the place of address units in linguistic and social spheres as well as directions for future research are defined.